Ukrainian criminal law at a crossroads: In pursuit of a new concept or on the path to its erosion? - Стрельцов, Євген Львович; Стрельцов, Є. Л.; Streltsov, Yevgen (My University, 2026)
The study is devoted to the analysis of the relationship between the traditional understanding of the subject of a criminal offense and modern transformations of this concept in the context of the development of the Ukrainian legal system. Historical (in particular, medieval), modern and potential future approaches to its interpretation are considered. Particular attention is paid to the concept of the so-called "illusory" or "phantom" subjects as theoretical constructs that reflect the change in ideas about the subject of a criminal offense. The thesis is substantiated about the decisive importance of the mentioned issues for understanding the essence and qualitative characteristics of criminal law, and the assumption is made that the corresponding conceptual "shifts" may indicate either a rethinking of basic doctrinal provisions or a gradual "erosion" of the fundamental principles of criminal law. Дослідження присвячене аналізу взаємозв’язку між традиційним розумінням суб’єкта кримінального правопорушення та сучасними трансформаціями цього поняття в контексті розвитку української правової системи. Розглянуто історичні (зокрема середньовічні), сучасні й потенційні майбутні підходи до його тлумачення. Особливу увагу приділено концепції так званих «ілюзорного» або «фантомного» суб’єктів як теоретичних конструкцій, що відображають зміну уявлень про суб’єкта кримінально-протиправного посягання. Обґрунтовується теза про визначальне значення зазначеної проблематики для розуміння сутності та якісних характеристик кримінального права, а також висловлюється припущення, що відповідні концептуальні «зрушення» можуть свідчити або про переосмислення базових доктринальних положень, або про поступову «ерозію» фундаментальних принципів кримінального права.
Streltsov Y. L. Ukrainian criminal law at a crossroads: In pursuit of a new concept or on the path to its erosion? / Y. L. Streltsov // JOR Jahrbuch für Ostrecht. - 2025. - № 66. - С. 13-44. - Режим доступу: https://hdl.handle.net/11300/31470
Keywords: перехідний стан; кримінальне право України; суб’єкт кримінального правопорушення; винність; індивідуальна відповідальність; юридична особа; штучний інтелект; «ілюзорний» («фантомний») суб'єкт; transitional state; criminal law of Ukraine; subject of criminal offense; guilt; individual responsibility; legal entity; artificial intelligence; "illusory" ("phantom") subject